Economics of local materials as base fluids in the formulation of an oil based mud (2019)
The use of drilling fluid is an important aspect in drilling operations as its critical to ensure a safe and productive oil or/ and gas well. In the bid to protect the environment and reduce environmental pollution resulting from drilling activities while using the No. 2 diesel, it is necessary to search for an alternative that will be suitable, locally available, easily affordable vegetable oils which is environmentally friendly and non-toxic as base fluid. This study is aimed at investigating the properties and economics analysis of the use of non-toxic, biodegradable locally obtainable oil from the palm kernel seed (Oil X) and coconut (Oil Y) as base fluid in the formulation of an Oil Based Mud. The rheological and filtration properties of the mud samples were evaluated using the API Recommended Standard, while the economics analysis was performed using the Net Present Value (NPV) and discounted profit to investment ratio (DPI) models. The results of the rheological, filtration and physiochemical properties for both X-OBM and Y-OBM, showed the possibility of the use of oil X or Y as base fluid as against No. 2 diesel. The result from the NPV model showed that the use of oil X or Y provided a higher NPV compared to those of No. 2 diesel mud even though the cost of No. 2 diesel was lower than those of X and Y oils. Also the discounted profit to investment ratio (DPI) was also better for mud formulated from the vegetable oil muds Although the initial cost of formulating mud samples using oil X or Y compared to No. 2 diesel Oil Base Muds (OBM) seems higher, consideration of their fire capacity resistance, nonimpact on the environmental and the cost of disposal of OBM the application of vegetable oil X or Y is more viable than No. 2 diesel in the industry